Audience-Aware Credibility: From Understanding Audience to Establishing Credible Blogs - Rieh, Soo Young; Jeon, Grace YoungJoo; Yang, Ji Yeon; Lampe, Clifford (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
This study examines how bloggers establish and enhance the credibility of their blogs through a series of blogging practices. Based on an analysis of interviews with 22 independent bloggers who blog on a range of topics, we present audience-aware credibility as a theoretical construct. Audience-aware credibility is defined as how bloggers signal their credibility based on who they think their audience is and how they provide value to that perceived audience. The analysis of bloggers’ credibility constructs, conceptualizations of audience, and perceived blog value identified four types of bloggers who constructed audience-aware credibility in distinctive ways: Community Builder, Expertise Provider, Topic Synthesizer, and Information Filterer. We then report on these bloggers’ blogging practices for establishing credibility and strategies for interacting with their audience to enhance credibility. The contributions of this study are to expand credibility constructs for social media research and to demonstrate the role of credibility perceptions in content contributors’ online activities. The findings reveal that a multi-dimensional construct of audience-aware credibility serves as a driving factor influencing and shaping blogging practices of all four types of bloggers. Copyright © 2014, Association for the Advancement of Artificial Intelligence (www.aaai.org). All rights reserved.